Coordinated control strategy for vehicle electro-hydraulic compound steering system. (February 2021) - Guo, Zhiqiang; Wu, Haixiao; Zhao, Wanzhong; Wang, Chunyan
In order to reduce steering energy consumption and improve steering feeling of heavy commercial vehicle, a novel electro-hydraulic compound steering system is proposed, which combines the function of electro-hydraulic power steering and electric power steering. The electro-hydraulic compound steering system dynamic model is established and the coordinated control strategy of dual actuators is proposed by analyzing the structure and dynamic characteristics of electro-hydraulic compound steering system. The genetic algorithm is used to optimize the steering assist torque distribution, and an Elman neural network predictive controller with fuzzy compensation is designed to solve the nonlinear problem of the electro-hydraulic compound system. Finally, the simulation is carried out by using Amesim/Simulink. The simulation results show that the coordinated control strategy designed in this paper enables the electro-hydraulic compound steering system significantly better than the traditional electro-hydraulic power steering system in steering feeling and energy consumption.